Pemberdayaan masyarakat berbasis ekonomi digital untuk meningkatkan pendapatan masyarakat pulau salemo kabupaten pangkep sulawesi selatan - Rosnaini Daga; Moh. Hatta; Abdul Samad; Fadliyani Nawir; Adi Sutanto; Vina Salviana Darvina Soedarwo; Oman Sukmana; Ruli Inayah Ramadhan; Rahadi (LPPMPK-Sekolah Tinggi Teknologi Muhammadiyah Cileungsi, 2023)
Salemo Island, one of the islands held by Pangkep Regency, is also referred to as Ulama Island since it has produced numerous Ulama in South Sulawesi and serves as a location for religious study. However, Salemo Island's religious beliefs are starting to change. This is the context in which the Kosabangsa Team decided to conduct Kosabangsa on Salemo Island. The goal to be achieved with the Kosabangsa Program is to make Salemo Island a religious tourism island by restoring religious values to Salemo Island. The process involves mapping the Salemo Island Asset Based Development Community, followed by Focus Group Discussions (FGD) tailored to partner needs, such as communication FGD, social media promotion FGD, seafood processing FGD (making shredded crab and shredded tuna), organizing marine product production house, and establishing a tourism awareness community group (POKDARWIS) on Salemo Island, Physical Strengthening through Salemo Island Stirytelling, an Island Website, and Pier Repair funded by the Regional Government of Pangkep Regency. The implementation of this Kosabangsa led to an increase in tourists to Salemo Island as well as a growth in the group of PKK women who make up the UMKM group who are MSME actors and operate a home business. IBK Nitro's partnership with UMM Malang through the Kosabangsa (Social Collaboration to Build the Nation) initiative significantly benefited the Salemo Island Community by providing training techniques for the UMKM Community in collaboration with PKK moms, Mosque Youth, and Salemo Island Bumdes